Novel electromagnetic oscillation method for uniform grain refinement and mechanical properties enhancement of flat-shaped aerospace components - Zong-sheng Xie; Xin Hao; Guo-huai Liu; Hang Zheng; Ye Wang; Chu-shan Yi; Zhao-dong Wang (Materials & Design)
Uniform fine grain structure is essential for enhancing the mechanical properties of flat-shaped aerospace components at the typical working temperature of 870 °C. However, the issue of grain coarsening after investment casting has remained intractable, necessitating reliable and efficient grain refinement methods. In this study, magnetic field distributions are simulated by ANSYS Maxwell, resulting in the design of three self-developed optimized electromagnetic oscillation (EMO) devices for grain refinement of different-sized flat-shaped aerospace components. The results show that the position of high magnetic field regions can be controlled by adjusting the iron core and hoop structure, ensuring magnetic field intensities > 70 KA/m in regions requiring grain refinement. The reliability of simulations is verified by successfully producing castings with uniform and fine equiaxed grains. Meanwhile, the tensile samples prepared with the EMO device under the 200A/20 Hz EMO process exhibit a 98.15 % reduction in grain size compared to direct casting, with strength properties slightly improved and elongation and section shrinkage significantly increased by 102.9 % and 110.9 %, respectively, at 870 °C. Grain refinement caused by EMO facilitated uniform deformation distribution, allowing samples to withstand larger deformations, causing the effect of deformation strengthening to outweigh the grain boundary strength reduction, thus enhancing strength properties.